Problems & solutions in signals, networks and transforms - Raja Mohd. Taufika Raja Ismail; Fairuz Rizal Mohamad Rashidi (Penerbit Universiti Malaysia Pahang, 2011)
The contents of this book have been organized to present the subject matter mainly in the way of solving circuit problems.